Hubungan Antara Pengetahuan Tentang Diare Dengan Perilaku Ibu Dalam Pencegahan Kejadian Penyakit Diare Pada Balita Diwilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu - Muqaromah, Asmi; Arfianti, Mariza; Pebriani , Emi (Jurnal Kesehatan Mitra Sekawan, 2025)
According to the United Nations Children's Fund (UNICEF) and World Health Organization (WHO) (2019), every year 1.9 million children under five die from diarrhea worldwide. According to the Health Office of Bengkulu Province (2022), Bengkulu City has 6,326 cases of diarrhea in toddlers. Objective : This study aims to determine the correlation between knowledge about diarrhea and maternal behavior in preventing the occurrence of diarrheal disease in toddlers in the working area of Jembatan Kecil Health Center in Bengkulu City. The method used was analytic research method and cross sectional design. Data were collected by distributing questionnaires to 58 respondents, namely mothers who have toddlers in the working area of Jembatan Kecil Health Center in Bengkulu City. The sampling technique used Accidental Sampling. The results of the Chi-Square test calculation, if the p value <0.05. The results of the univariate test analysis included almost half of the respondents (41.1%) had sufficient knowledge and almost half of the respondents (39.7%) had sufficient behavior. Bivariate analysis results that there is a correlation between knowledge about diarrhea with maternal behavior in preventing the occurrence of diarrheal disease in toddlers where the p value (0.000). This study has toddlers in order to add insight and information about knowledge about diarrhea with maternal behavior in preventing the occurrence of diarrheal disease in toddlers.